Body mapping: A novel tool for psychiatrists - Vyasa Immadisetty (Archives of Mental Health, 2012)
Background: Body mapping is a creative therapeutic tool that brings together bodily experience and visual artistic expression. Initially, it was used by health and safety for detecting unspoken injuries in workforce, musicians to improve posture and coordination while decreasing injury. Its effectiveness in improving communication was exploited by allied health bodies for talking about sensitive sexual health issues and improve health awareness in Uganda, Kenya, India and Thailand. The technique involves patients to represent psychosomatic symptoms, body images, aches and pains, onto a chart (body map) using colours, pictures, symbols and words to represent various experiences. This is akin to a psychological enquiry where the clinician exploits the exercise to develop an understanding of the patient's psychopathology as well as foster a relationship. Case description: The author reports a case of middle aged man of Afro Caribbean origin with psychotic illness who was successfully treated by utilizing the concepts of body-mind mapping. This paper highlights the benefits of using body mapping in psychiatric practice by way of improved communication between patient and therapist to explore psychosomatic as well as builds therapeutic relationship. Discussion: Body mapping has been used by therapists in diverse areas like eating disorder, trauma etc. It helps to externalise somatic-emotional experience, to make meaning through the creative process of symbolization. This technique may be useful in cases of the chronic illnesses to aid engagement, compliance and insight. The wide prevalence of psychosomatic complaints across the world indicates the necessity for alternative models of interactive communication other than a language based psychiatric interview in all situations. Conclusion: Body mapping can be a useful clinical communication tool. When used appropriately, it has the potential to improve insight and compliance in psychiatric patients.